2012
DOI: 10.1007/s10815-012-9830-y
|View full text |Cite
|
Sign up to set email alerts
|

Day 3 embryo transfer may have better pregnancy outcomes in younger than 35-year-old patients with poor ovarian response

Abstract: Objective To explore the pregnancy outcomes of embryo transfer with D2 or D3 embryos in patients with poor ovarian response. Methods The pregnancy outcomes of 620 patients who had poor ovarian response and underwent the first in vitro fertilization-embryo transfer (IVF-ET) were retrospectively analyzed. Of the 620 cycles, all available fresh D2 embryos were used in 365 cycles (day 2 embryo transfer) and all available fresh D3 embryos were used in 255 cycles (day 3 embryo transfer) without superfluous embryos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
5
2
1
Order By: Relevance
“…However, Zhu et al showed that the clinical pregnancy rate of D3 embryo transplantation was higher than that of D2 embryo transplantation in patients younger than 35 years of age with a normal or poor ovarian response. 6 Unlike the studies mentioned above, the present study showed that D2 embryo transfer had similar rates of positive hCG, clinical pregnancy, miscarriage, and live birth to D3 embryo transfer in patients with only one 2PN, regardless of the patient's age. This discrepancy between studies may be due to differences in the study design and grouping criteria.…”
Section: Discussioncontrasting
confidence: 79%
“…However, Zhu et al showed that the clinical pregnancy rate of D3 embryo transplantation was higher than that of D2 embryo transplantation in patients younger than 35 years of age with a normal or poor ovarian response. 6 Unlike the studies mentioned above, the present study showed that D2 embryo transfer had similar rates of positive hCG, clinical pregnancy, miscarriage, and live birth to D3 embryo transfer in patients with only one 2PN, regardless of the patient's age. This discrepancy between studies may be due to differences in the study design and grouping criteria.…”
Section: Discussioncontrasting
confidence: 79%
“…Interestingly, prior studies have suggested that poor ovarian response may impact clinical pregnancy rates depending on D2 or D3 [9,10]. Xin and colleagues further suggested a possible benefit to D3 transfer amongst younger women with fewer than six oocytes retrieved [10]. Our data in contrast illustrate that neither ovarian response (given the low number of oocytes retrieved in the fertilization rate ≥ 50% subgroup) nor ovarian reserve (determined by AMH) impact clinical outcomes for D2 vs. D3 embryo transfers.…”
Section: Discussioncontrasting
confidence: 58%
“…Additionally, women with a fertilization rate ≥ 50%, corresponding to those with fewer than five oocytes retrieved based on our study inclusion criteria, had similar outcomes regardless of transfer. Interestingly, prior studies have suggested that poor ovarian response may impact clinical pregnancy rates depending on D2 or D3 [9,10]. Xin and colleagues further suggested a possible benefit to D3 transfer amongst younger women with fewer than six oocytes retrieved [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Введение: Применение гормональной стимуляции суперовуляции в программах вспомогательных репродуктивных технологий (ВРТ), позволяет увеличить количество полученных ооцитов на цикл, и соответственно, доступных эмбрионов и бластоцист для выбора на перенос или криоконсервацию, что в конечном итоге позволяет увеличить эффективность программ при лечении бесплодия. Таким образом, благодаря, внедрению и совершенствованию протоколов гормональной стимуляции суперовуляции, эффективность лечения методами ВРТ увеличилась с 20-30 до 40-50% [1]. Однако, несмотря на очевидное преимущество стимуляции суперовуляции в отношении увеличения числа фолликулов и количества получаемых ооцитов, отмечается негативное влияние гормональных препаратов на качество эндометрия [2].…”
unclassified